Radiographic evaluation of the forelimbs and hind limbs of marmosets (Callithrix spp.) - de Souza Siragusi, Rafael H. [UNESP]; Rahal, Sheila C. [UNESP]; da Silva, Jeana P. [UNESP]; Mamprim, Maria J. [UNESP]; Rolim, Luna S. [UNESP]; Teixeira, Carlos R. [UNESP]; de Camargo, Barbara W. D. F. [UNESP]; Monteiro, Frederico O. B. (Wiley, 2020)
Background: The maintenance of marmosets in captivity may trigger various disorders. The objective of this study was to provide a radiographic evaluation of the forelimbs and hind limbs of marmosets rescued from illegal wildlife trade and maintained in captivity. Methods: Fourteen marmosets were studied. Results and conclusions: Three marmosets were apparently normal. Of the eleven marmosets with radiographic changes in the hind limbs, five had pelvic narrowing and bilateral varus deviation of the femur, with one suggestive of rickets and another of osteomalacia. The other marmosets showed changes such as malunion of acetabular fracture, transtibial amputation, tibial antecurvatum, and knee osteoarthritis. Six marmosets showed alterations in the forelimbs such as radius fracture, scapulohumeral subluxation, and elbow joint incongruence. In conclusion, 78.57% of the marmosets had bone and/or joint changes detected by plain radiography, which were found predominantly in the hind limbs and without impediment to locomotion in captivity.
Keywords: bone; disease; imaging; primates; wildlife